Fixed point results for single and multivalued three-points contractions - Jleli, Mohamed; Petrov, Evgeniy; Samet, Bessem (Nonlinear Analysis: Modelling and Control, 2025)
In this paper, we are concerned with the study of the existence of fixed points for single and multivalued three-points contractions. Namely, we first introduce a new class of singlevalued mappings defined on a metric space equipped with three metrics. A fixed point theorem is established for such mappings. The obtained result recovers that established recently by the second author [E. Petrov, Fixed point theorem for mappings contracting perimeters of triangles, J. Fixed Point Theory Appl., 25(3):74, 2023] for the class of single-valued mappings contracting perimeters of triangles. We next extend our study by introducing the class of multivalued three points contractions. A fixed point theorem, which is a multivalued version of that obtained in the above reference, is established. Some examples showing the validity of our obtained results are provided.
Keywords: fixed points; single-valued three-points contractions; multivalued three-points contractions; mappings contracting perimeters of triangles